The Herschel Bright Sources (HerBS): sample definition and SCUBA-2 observations - Bakx, Tom J.L.C.; Eales, S.A.; Negrello, M.; Smith, M.W.L.; Valiante, E.; Holland, W.S.; Baes, M.; Bourne, N.; Clements, D.L.; Dannerbauer, H.; De Zotti, G.; Dunne, L.; et al. (Oxford University Press, 2018)
We present the Herschel Bright Sources (HerBS) sample, a sample of bright, high-redshift Herschel sources detected in the 616.4 deg2 Herschel Astrophysical Terahertz Large Area Survey. The HerBS sample contains 209 galaxies, selected with a 500 μm flux density greater than 80 mJy and an estimated redshift greater than 2. The sample consists of a combination of hyperluminous infrared galaxies and lensed ultraluminous infrared galaxies during the epoch of peak cosmic star formation. In this paper, we present Submillimetre Common- User Bolometer Array 2 (SCUBA-2) observations at 850 μm of 189 galaxies of the HerBS sample, 152 of these sources were detected. We fit a spectral template to the Herschel-Spectral and Photometric Imaging Receiver (SPIRE) and 850 μm SCUBA-2 flux densities of 22 sources with spectroscopically determined redshifts, using a two-component modified blackbody spectrum as a template.We find a cold- and hot-dust temperature of 21.29+1.35−1.66 and 45.80+2.88−3.48 K, a cold-to-hot dust mass ratio of 26.62+5.61−6.74 and a β of 1.83+0.14−0.28. The poor quality of the fit suggests that the sample of galaxies is too diverse to be explained by our simple model. Comparison of our sample to a galaxy evolution model indicates that the fraction of lenses are high. Out of the 152 SCUBA-2 detected galaxies, the model predicts 128.4 ± 2.1 of those galaxies to be lensed (84.5 per cent). The SPIRE 500 μm flux suggests that out of all 209 HerBS sources, we expect 158.1 ± 1.7 lensed sources, giving a total lensing fraction of76 per cent.